Asymmetric behavior of current-induced magnetization switching in a magnetic tunnel junction: Non-equilibrium first-principles calculations - Araidai, Masaaki; Yamamoto, Takahiro; Shiraishi, Kenji (Applied physics express, 2014)
We investigated the microscopic mechanisms of current-induced magnetization switching (CIMS) in an Fe/MgO(001)/Fe/Ta magnetic tunnel junction using non-equilibrium first-principles calculations. We found that the change in the magnetization configuration from antiparallel (AP) to parallel (P) can be realized with a lower electrical power than that from P to AP. From detailed analyses of the density of states subject to a finite bias voltage, we clarified that the asymmetric behavior originates from the difference in the electron scattering processes between switching directions.